Judicial acts and investment treaty arbitration - Demirkol, Berk (Cambridge international trade and economic law., 2018)
Judicial acts of states are becoming increasingly subjected to international investment claims. This book focuses on distinctive particularities of these claims. Although there are no special responsibility regimes for different functions of the state, the application of investment treaty standards and the threshold for their breach may vary depending on the function involved. Accordingly, in order for the state to incur responsibility for a wrongful act committed in the exercise of its judicial function, there are some specific conditions that should be met: the investor must establish that the state is responsible for a breach attributable to the state; the investment tribunal has jurisdiction over the particular dispute; and the damage that the investor has suffered is a result of the particular breach. Berk Demirkol addresses questions in relation to the substance, jurisdiction, admissibility, and remedies in cases where state responsibility arises from a wrongful judicial act.